N-Ethyl-N-Nitrosourea (ENU) Mutagenesis Reveals an Intronic Residue Critical for Caenorhabditis elegans 3′ Splice Site Function in Vivo. Issue 6 (1st June 2016) - Itani, Omar A; Flibotte, Stephane; Dumas, Kathleen J; Guo, Chunfang; Blumenthal, Thomas; Hu, Patrick J
Abstract: Metazoan introns contain a polypyrimidine tract immediately upstream of the AG dinucleotide that defines the 3′ splice site. In the nematode Caenorhabditis elegans, 3′ splice sites are characterized by a highly conserved UUUUCAG/R octamer motif. While the conservation of pyrimidines in this motif is strongly suggestive of their importance in pre-mRNA splicing, in vivo evidence in support of this is lacking. In an N -ethyl- N -nitrosourea (ENU) mutagenesis screen in Caenorhabditis elegans, we have isolated a strain containing a point mutation in the octamer motif of a 3′ splice site in the daf-12 gene. This mutation, a single base T-to-G transversion at the -5 position relative to the splice site, causes a strong daf-12 loss-of-function phenotype by abrogating splicing. The resulting transcript is predicted to encode a truncated DAF-12 protein generated by translation into the retained intron, which contains an in-frame stop codon. Other than the perfectly conserved AG dinucleotide at the site of splicing, G at the –5 position of the octamer motif is the most uncommon base in C . elegans 3′ splice sites, occurring at closely paired sites where the better match to the splicing consensus is a few bases downstream. Our results highlight both the biological importance of the highly conserved –5 uridine residue in the C. elegans 3′ splice site octamer motif as well as the utility of using ENU as a mutagen to study the function of polypyrimidine tracts and other AU- or AT-rich motifs in vivo .